2017
DOI: 10.1016/j.fertnstert.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

DNAH1 gene mutations and their potential association with dysplasia of the sperm fibrous sheath and infertility in the Han Chinese population

Abstract: These DNAH1 gene mutations may be associated with DFS and infertility in the Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 24 publications
5
72
0
Order By: Relevance
“…Thus, the mutations in DNAH2 gene may be the main causes of the ablation of DNAH2 protein and the defects of flagella in patient's spermatozoa. Missense/nonsense, frameshift and essential splice‐site mutations in DNAH1 , which encodes another axonemal inner arm DHC protein, could also significantly decrease the protein expression and cause the MMAF phenotype . These studies in DNAH1 and DNAH2 reveal an essential role of DHC family proteins in the maintenance of the structural integrity of the flagella and suggest that other DHC‐encoding genes with unidentified functions might be involved in the sperm flagellar defects phenotype.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the mutations in DNAH2 gene may be the main causes of the ablation of DNAH2 protein and the defects of flagella in patient's spermatozoa. Missense/nonsense, frameshift and essential splice‐site mutations in DNAH1 , which encodes another axonemal inner arm DHC protein, could also significantly decrease the protein expression and cause the MMAF phenotype . These studies in DNAH1 and DNAH2 reveal an essential role of DHC family proteins in the maintenance of the structural integrity of the flagella and suggest that other DHC‐encoding genes with unidentified functions might be involved in the sperm flagellar defects phenotype.…”
Section: Discussionmentioning
confidence: 89%
“…Until now, only a few gene autosomal variants have been reported to cause MMAF phenotype in infertile man, such as AKAP4 , DNAH1 , CFP43 , CFP44 and FISP2 . Among these genes, DNAH1 is believed to be the main genetic contributor .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have indicated that biallelic mutations in DNAH1, CFAP43 and CFAP44, which occur with a frequency that is independent of genetic origin, cause the majority of MMAF cases (Amiri-Yekta et al, 2016;Ben Khelifa et al, 2014;Sha et al, 2018;Sha, Yang, et al, 2017;Tang et al, 2017;Wang et al, 2017). Multiple studies have indicated that biallelic mutations in DNAH1, CFAP43 and CFAP44, which occur with a frequency that is independent of genetic origin, cause the majority of MMAF cases (Amiri-Yekta et al, 2016;Ben Khelifa et al, 2014;Sha et al, 2018;Sha, Yang, et al, 2017;Tang et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic testing by whole-exome sequencing identified 12 MMAF patients with homozygous or compound heterozygous DNAH1 mutations (DNAH1 + group; Sha, Yang, et al, 2017) and six patients with biallelic CFAP44 (CFAP44 + group) or CFAP43 mutations (Sha et al, 2018). MMAF patients and non-MMAF subjects (age-matched control group) were recruited from the Xiamen Maternity and Child Care Hospital (Xiamen, China) and the Affiliated Yantai Yuhuangding Hospital of Qingdao University (Qingdao, China).…”
Section: Patients and Controlsmentioning
confidence: 99%
See 1 more Smart Citation